STI in History: Korean STI policies in technology catching-up stage - Hong, Sungjoo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
1. Introduction Korea enhanced its global status through the industrialization of the 1960s and the 1970s; however, there was also an increased economic and social burden due to the growth. The 1979 energy crisis caused oil prices to soar and put the domestic heavy chemical industry (a consumer of imported oil) in difficulty. Economically, the Korean government recognized that an export-oriented industrial structure that depended on imported raw materials was no longer sustainable. In addition, from a social aspect, it was difficult to maintain an industrial structure that was dependent on low-wage labor because of a burgeoning labor movement and a more active prodemocracy movement. In the 1980s, the Korean government sought to find “technology solutions” to the problems caused by export-oriented industrialization. The government “technology drive” strategy established a common goal to replace the existing “export drive”, and achieve the “technology catching up” with advanced countries in the public and private sector. Subsequently, Korea quickly became a country of high-tech industries. In the process of technology catching up, light industries (such as textiles) that used to contribute greatly to the exporting business, started to decline; however, high-tech industries (such as electronics, computers, and communications) emerged as key industries.